New insights on the Monte Fenera Palaeolithic, Italy: Geoarchaeology of the Ciota Ciara cave. Issue 4 (15th November 2018) - Angelucci, Diego E.; Zambaldi, Maurizio; Tessari, Umberto; Vaccaro, Carmela; Arnaud, Julie; Berruti, Gabriele L.F.; Daffara, Sara; Arzarello, Marta
Abstract: Monte Fenera is a mostly carbonate hill at the southern border of the Western Alps. It hosts several archaeological sites, among them karstic caves bearing evidence of Palaeolithic occupation. These sites have a long history within Alpine archaeology—having been explored since the 19th century—but information on their stratigraphy, chronology, and formation remains incomplete. They are among the few cave‐sites occupied before the Alpine Last Glacial Maximum in the area, and their study is crucial for understanding human occupation and regional environmental evolution during the Pleistocene. Here we focus on Ciota Ciara, a cave formed in Triassic dolostone, and in particular on the Middle‐to‐Upper Pleistocene succession unearthed at its south‐western entrance since 2009. This succession was analyzed by means of several geoarchaeological methods including stratigraphy, routine sediment analyses, and archaeological micromorphology. Our study shows that sediment accumulation was due to the repeated occurrence of concentrated flow and runoff events from the karstic system alternating with episodes of wall disintegration and short phases of surface stabilization. Post‐depositional processes include frost action, hydromorphism, and diagenesis that have selectively affected the archaeological remains. The results of the study shed light on site formation and have relevance for Pleistocene cave archaeology more widely in the southern Western Alps.